2015
DOI: 10.1111/imj.12675
|View full text |Cite
|
Sign up to set email alerts
|

Thromboprophylaxis in patients undergoing total hip and knee arthroplasty: a review of current practices in an Australian teaching hospital

Abstract: The proportion of study patients receiving thromboprophylaxis compares favourably with prior research. The overall incidence of VTE is higher than that demonstrated in major orthopaedic trials. Inadequate duration of chemoprophylaxis remains a potential area of improvement. Extended prophylaxis should be prescribed as per current guidelines. Comparison between efficacy and safety of various agents is the subject of future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…The overall incidence was 4.7% (19/402), with the majority occurring following TKA (6.5%, 13/200). 19 This frequency was congruent with our findings of 6.7% (33/493).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The overall incidence was 4.7% (19/402), with the majority occurring following TKA (6.5%, 13/200). 19 This frequency was congruent with our findings of 6.7% (33/493).…”
Section: Discussionsupporting
confidence: 93%
“…The incidence of in‐hospital VTE in this centre has previously been examined in patients undergoing TKA and THA. The overall incidence was 4.7% (19/402), with the majority occurring following TKA (6.5%, 13/200) . This frequency was congruent with our findings of 6.7% (33/493).…”
Section: Discussionsupporting
confidence: 87%
“… 17 25 Lower compliances for medical than surgical patients in the ENDORSE study and the regional hospital are consistent with the more complex indications in medical patients, and have been noted elsewhere. 26 No equivalent Australian studies could be found for indicators associated with management of suspected or confirmed DVT or PE (CTA compliance 64%), or patients with a documented discharge plan and a date for cessation of treatment (CTA compliance 46%), but it would seem reasonable to conclude that both of these areas of practice also require attention.…”
Section: Discussionmentioning
confidence: 99%
“…Pow and Vale's 20 study in one private hospital in Australia looked at 400 patients undergoing total hip and knee arthroplasty, who received chemical thromboprophylaxis for a minimum of 10 to 14 days. Almost half received LMWH and 125 received aspirin while in hospital.…”
Section: Resultsmentioning
confidence: 99%